2013
DOI: 10.1111/bph.12213
|View full text |Cite
|
Sign up to set email alerts
|

5‐Chloroindole: a potent allosteric modulator of the 5‐HT3 receptor

Abstract: BACKGROUND AND PURPOSEThe 5-HT3 receptor is a ligand-gated ion channel that is modulated allosterically by various compounds including colchicine, alcohols and volatile anaesthetics. However the positive allosteric modulators (PAMs) identified to date have low affinity, which hinders investigation because of non-selective effects at pharmacologically active concentrations. The present study identifies 5-chloroindole (Cl-indole) as a potent PAM of the 5-HT3 receptor. EXPERIMENTAL APPROACH5-HT3 receptor function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
(59 reference statements)
4
15
0
Order By: Relevance
“…We previously demonstrated that when 5‐HT 3 A receptors were completely desensitized by prolonged application of 5‐HT, subsequent application of Cl‐indole generated an inward current indicative of Cl‐indole being able to reactivate desensitized receptors (Newman et al , ) (see also Figure ). We therefore tested whether Cl‐indole could modulate receptor resensitization using a dual pulse protocol; a single prolonged application of 5‐HT (10 μM, 20 s) induced receptor desensitization (Figure A).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We previously demonstrated that when 5‐HT 3 A receptors were completely desensitized by prolonged application of 5‐HT, subsequent application of Cl‐indole generated an inward current indicative of Cl‐indole being able to reactivate desensitized receptors (Newman et al , ) (see also Figure ). We therefore tested whether Cl‐indole could modulate receptor resensitization using a dual pulse protocol; a single prolonged application of 5‐HT (10 μM, 20 s) induced receptor desensitization (Figure A).…”
Section: Resultsmentioning
confidence: 93%
“…As well as orthosteric agonism, allosteric modulation of the 5‐HT 3 receptor has been reported by compounds as diverse as alcohols (Downie et al , ; Bentley and Barnes, ; Stevens et al , ), cannabinoids (Barann et al , ), indole derivatives (Parker et al , ; Van Hooft et al , ; Newman et al , ), terpenes (Lansdell et al , ; Ziemba et al , ), benzamides (Jørgensen et al , ) and the class of novel negative allosteric modulators typified by PU02 (Trattnig et al , ). A number of these modulators appear to have their effect via a site (or sites) in the transmembrane domain [e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, positive allosteric modulation of 5-HT 3 Rs has been observed with alcohols (Machu and Harris, 1994), volatile anesthetics (Machu and Harris, 1994), colchicine (de OliveiraPierce et al, 2009), and 5-chloroindole (Newman et al, 2013). In addition, menthol (a monoterpene) has been shown to act as an allosteric inhibitor of human 5-HT 3 Rs (Ashoor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such compounds include verapamil (Hargreaves et al, 1996), cannabinoids (Barann et al, 2002), cannabidiol (Yang et al, 2010), hydrocortisone (Corradi et al, 2011), menthol (Ashoor et al, 2013), and PU02 (6-[(1-naphthylmethyl)thio]-9H-purine) (Trattnig et al, 2012). A variety of positive allosteric modulators of 5-HT 3 Rs have also been identified, including alcohols (Zhou and Lovinger, 1996), 5-hydroxyindole (van Hooft et al, 1997) colchicine (de Oliveira-Pierce et al, 2009), and 5-chloroindole (Newman et al, 2013).…”
mentioning
confidence: 99%